Parafilariosis in cattle in Malatya and environs - Saki, CE; Sevgili, M; Özer, E (Scientific Technical Research Council Turkey, 1999)
This study was conducted in cattle on Malatya and environs. A total of 432 cattle were clinically examined for cattle parafilariosis. Cattle parafilariosis was clinically diagnosed in 22 cattle in August 1995, six cattle in September 1995, two cattle in July 1996, one cattle in August 1996, and one cattle in August 1997. Thirty-two out of 432 cattle (7.4%) were diagnosed as having the disease. Upon the microscopic examination of blood samples from wounds. 18 microfilariae were found whereas no eggs were found in 10 cattle. The disease was more widespread in 1-2 year-old cattle (46.8%) and females (68.7%) than in male animals.
Malatya ve Yöresi Si?irlannda Parafilariosis
Keywords: Parafilaria bovicola; cattle